2021
DOI: 10.7150/ijbs.53982
|View full text |Cite
|
Sign up to set email alerts
|

A rapid screening classifier for diagnosing COVID-19

Abstract: Rationale: Coronavirus disease 2019 (COVID-19) has caused a global pandemic. A classifier combining chest X-ray (CXR) with clinical features may serve as a rapid screening approach. Methods: The study included 512 patients with COVID-19 and 106 with influenza A/B pneumonia. A deep neural network (DNN) was applied, and deep features derived from CXR and clinical findings formed fused features for diagnosis prediction. Results: The clinical features of COVID-19 and influenza showed different patterns. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…There have been complex attempts to better predict the presence of COVID-19 by creating artificial intelligence (AI) programs which process clinical data as well as imaging techniques. Xia et al [20] describe that when considering 52 clinical and laboratory coefficients, e.g., disseminated intravascular coagulation, d-dimer, procalcitonin, enlarged lymph nodes or rhabdomyolysis together with CXR features, sensitivity increased to 94% and specificity to 75%. However, the complex information required is hardly available in the setting of an ER before deciding whether a possible COVID-19 patient should be hospitalized or not.…”
Section: Discussionmentioning
confidence: 99%
“…There have been complex attempts to better predict the presence of COVID-19 by creating artificial intelligence (AI) programs which process clinical data as well as imaging techniques. Xia et al [20] describe that when considering 52 clinical and laboratory coefficients, e.g., disseminated intravascular coagulation, d-dimer, procalcitonin, enlarged lymph nodes or rhabdomyolysis together with CXR features, sensitivity increased to 94% and specificity to 75%. However, the complex information required is hardly available in the setting of an ER before deciding whether a possible COVID-19 patient should be hospitalized or not.…”
Section: Discussionmentioning
confidence: 99%
“…Most literature studies use AI in CXR to distinguish between COVID-19 and other pneumonia and healthy patients [53][54][55]. Xia et al described the use of a rapid and economic classifier for screening of COVID-19 from influenza-A/B pneumonia which combined CXR (or CT-localizer scanogram) data with clinical features, with 91.5% sensitivity and 81.2% specificity and an AUC of 0.971 (95% CI 0.964-0.980) [56].…”
Section: Artificial Intelligence In Chest X-raymentioning
confidence: 99%
“…Previous studies on influenza diagnosis using AI remain few. Xia et al reported an AI-based classifier distinguishing influenza from COVID-19 using chest X-ray images and clinical features with an AUC of 0.9 [ 17 ]. Choo et al reported the usefulness of the patient-generated health data obtained from a mobile health application to develop an AI-based screening tool for influenza [ 18 ].…”
Section: Discussionmentioning
confidence: 99%